Postgraduate students' experiences with learning management systems at a selected nursing education institution in KwaZulu-Natal Province - N G Mtshali; A Harerimana; V N Mdunge; Z M Mthembu (South African Medical Association, 2022)
Background. Learning management systems (LMS) are indispensable teaching and learning tools in nursing education, and in recent years, LMS have become a cornerstone to support online learning, particularly during the COVID-19 pandemic. The South African (SA) e-education policy requires every teacher and learner in the education and training sector to be information and communication technology (ICT)-capable, and able to use ICTs confidently and creatively to help develop the skills and knowledge they need as lifelong learners to achieve their personal goals and be full participants in their global communities. Objective. To investigate postgraduate students' experiences with learning management systems at a selected nursing education institution in KwaZulu-Natal Province, SA. Method. An exploratory, descriptive research design was used, and the whole population of 16 postgraduate nursing education students who were exposed to Moodle as a learning management system participated in the study. Qualitative data were collected through semi-structured interviews, followed by focus group discussions, with thematic analysis used to analyse data. Results. This was the first time that most participants had been exposed to an online learning course, and the experience made them feel empowered as it provided enabled reflection and deep learning. Participants indicated that the range of interactions and level of engagement determined the eventual level of knowledge constructed. The online facilitator played a central role in guiding and supporting students, and ensuring that they achieved the learning outcomes. The online learning benefits included increased socialisation, convenience and flexibility, asynchronicity and accessibility of learning material. The challenges were the lack of real-time response, financial cost and technical issues. Conclusion. An intense ICT orientation for students is recommended to ensure that they are informed of the requirements before starting the online course. The online facilitators must be more visible in the online space, participate more often in discussions and stimulate constructive dialogue.